Financial institutions management : a modern perspective - Saunders, Anthony (Boston : Irwin/McGraw-Hill, 2000)
Focuses on the risks faced by managers of financial institutions and the methods and markets through which these risks are managed. Pertinent information regarding non-bank financial institutions provides a more holistic view of the challenges raised by factors such as interest rates.
International edition
Includes bibliographical references and index.
opc 27/09/16
Loans
Keywords: Financial institutions; Risk management---Management; Financial services industry---Management; Risk management; United States of America